The Influence of Social Capital on Reading Interest among Book Party Participants - Wulandari, Dina; Hak, Ade Abdul (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: The low reading interest of Indonesian society remains a crucial problem in the era of rapid development of digital information flow. Reading communities are an alternative that can be used to overcome this problem because within the community there is social capital that can be utilized by its members. One community that shows a high social capital is Jakarta Book Party Community.Objective: This study aims to determine the effect of social capital consisting of norms, trust, and social networks on the reading interest of Jakarta Book Party Community participants.Methods: This study uses a quantitative approach with a data collection method through the distribution of questionnaires to 91 samples who are active participants in Jakarta Book Party activities.Results: The results of this study indicate that partially the trust variable (b = 1.193; sig. = 0.000) and the social network variable (b = 0.795; sig. = 0.000) have a positive and significant effect on reading interest, while the norm variable (b = -1.032; sig. = 0.000) actually has a negative and significant effect on reading interest. Meanwhile, simultaneously, the variables of norms, trust, and social networks (F count 112.955 > F table 2.71; sig. = 0.000 < 0.05) have a significant influence on the reading interest of Jakarta Book Party participants.Conclusion: This research confirms that trust and social networks have a significant and positive influence on the reading interest of Jakarta Book Party participants, norms have a significant and negative influence on the reading interest of Jakarta Book Party participants.